Tracking The Lore Of Educational Objectives In Islamic Perspective Tense - Nandang Syarif; M. Ihsan; Agus Kurnia; Ade Jamarudin; Sarwedi Daulay (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Islamic education is a form of manifestation of the ideals of Muslims to preserve Islamic values for the next generation, so that the cultural-religious values aspired to can function and develop in society, so that Islamic educators try to form Muslim personalities that are in accordance with Islamic education goals. Islamic education is also based on the highest goal, which is to want students to be a blessing to all creatures. With this grace, it is expected to be able to spread the values of compassion by always advising one another on truth and patience. This research method uses library research and is descriptive, analytic and comparative. Source of data used in this research comes from primary and secondary data. Islamic education as in general education, trying to shape the human person must go through a long process, with results that cannot be known immediately. Many Islamic education experts provide an understanding of the purpose of education. There are those who formulate that the goal is something that is expected to be achieved after a business or activity is completed. While others say that the goal may point to futurity that is located at a certain distance that cannot be achieved except by trying to go through a certain process.